OPINION OF COACHES AND ATHLETES CONCERNING THE EXPECTATIONS FOR THE COACHES - Andras S. Szabo (Sport Scientific And Practical Aspects, 2025)
In the paper information is given about important parameters, expectations, concerning the role of the coach from point of view of coaches and athletes, based on evaluation of questionnaires. To the opinion of coaches from the investigated 10 different topics (physical abilities, mental abilities, transfer of the knowledge, ability to manage different age groups, ability of pedagogy, support the athletes, ready to help, motivation, outlook, behavior) the ability to transfer the knowledge, the ability of pedagogy and the knowledge (mental abilities) are the dominant parameters. To the opinion of athletes on the first place is similarly the ability to transfer the knowledge, however on the second place the mental abilities and on the third one the support the athletes.